Strong adsorption of cationic dyes by cucurbit[7]uril modified magnetic carbon nanotubes: Investigation on adsorption performance, reusability, and adsorption mechanism - Hu, Yujie; Zou, Changjun; Xiong, Tingting; Wang, Huihui (Journal of industrial and engineering chemistry (Seoul, Korea), 2023)
[Display omitted] In this work, a facile one-pot method was used to synthesize the co-modified carbon nanotube adsorbent (CB/MMCNT) of cucurbit[7]uril and Fe3O4. A series of characterizations were utilized to confirm the successful synthesis of the adsorbent. VSM and separation experiments demonstrated that the adsorbent exhibited excellent magnetic separation performance and could achieve rapid separation within 30 s. BET results show that the adsorbent has excellent specific surface area (67.438 m2/g). Subsequently, three cationic dyes, namely Methylene blue (MB), Malachite green (MG), and Gentian violet (GV), were utilized in batch adsorption experiments. A strong adsorption effect on cations is exerted by the adsorbent through hydrogen bonds, electrostatic interactions, π-π conjugation effects and hydrophobic interactions. Under the optimal conditions (pH = 6, T = 300 min, C0 = 1000 mg/L), the maximum adsorption capacity of CB/MMCNT to MB, MG, and GV was 851.5 mg/g, 720.2 mg/g, and 563.4 mg/g. The adsorption data could be well fitted by both the pseudo-second-order kinetic model (R2 > 0.99) and Langmuir isotherm model (R2 > 0.99). Thermodynamic data indicated that the adsorption process was spontaneous and endothermic. Moreover, the cyclic reuse performance of CB/MMCNT was evaluated through 7 cycles of recycling experiments, which demonstrated that it maintained a high dye removal rate (MB 84%, MG 78%, GV 81%), indicating its excellent reusability. Additionally, CB/MMCNT still maintained its impressive cationic dye removal performance (MB 95.8%, MG 92.7%, GV 92.2%) when tested in practical water environments. Overall, CB/MMCNT is a promising, environmentally friendly, efficient, and sustainable adsorbent for removing cationic dyes.